The Challenge of Reforming Budgetary Institutions in Developing Countries - Allen, Richard (IMF Working Papers; Working Paper, 2009)
The paper notes that the development of sound budgetary institutions in countries such as France, the U.K. and the U.S. has taken a very long time?200 years or more?and is still evolving. It discusses Douglass North's prediction?which is supported by available data?that institutional reform is also likely to be very slow in developing countries since the budget is especially prone to rent-seeking influences. Finally, the paper discusses the currently fashionable emphasis on complex, multiannual PFM reform strategies, which have been strongly promoted by the donor community; and advocates a simpler approach grounded on Schick's important principle of "getting the basics right." The paper identifies several areas where further research would be fruitful.